Cyclic behavior of buckling-controlled braces. (June 2016) - Shen, Jay; Seker, Onur; Sutchiewcharn, Narathip; Akbas, Bulent
Abstract: A parametric study is presented to quantify essential factors influencing cyclic behavior of a steel buckling-controlled brace (BCB) with a tube carrying axial load surrounded by an outer tube to control buckling of the load-bearing tube. A small-scale experiment helped observe overall cyclic behavior, and develop finite-element models for numerical simulations. The model-based simulations identified the interaction of the friction, gap and thickness ratio between the two tubes as the essential factor. The paper concludes that (1) the gap is a sensitive parameter influencing local and global buckling. The smaller the gap, the less likely the local and global buckling will occur, but the more participation of the outer tube in load bearing due to adverse interaction between the two tubes; (2) Friction between the two tubes is a very delicate factor because its impact on the cyclic behavior of BCB varies depending on thickness ratio and friction; (3) Thickness ratio of the two tubes decides the effectiveness of controlling buckling. The thickness ratio of 1.0 is sufficient to control global buckling, but a larger than 1.0 ratio is needed to control both local and global buckling; (4) Interaction among the gap, friction and thickness ratio is strong, and shall be considered in design; and (5) Optimal performance results from a system with smallest gap possible, low friction, and heavier outer tube. Some less optimal but lower costly design combinations may have moderate gaps and various outer tube sizes to control brace buckling within targeted drift limits in performance-based design. Highlights: An all-steel buckling-controlled brace (BCB) is found to be efficient in improving seismic performance of braced frames. Common shapes for both load-bearing and buckling controlling members make BCB easy to fabricate in practice. Interaction among three parameters, gap, thickness ratio, and friction coefficient in the BCB is strong. Better performance results from a near-zero gap, low friction, and a buckling controller heavier than load-bearing tube.